Assessment of User’s Satisfaction with use of National Library of Nigeria-Calabar Branch - Ekeng, Martina Ekpenyong; Etok, Nkereuwem John; Abua, Dymphina Anyingang (Communicate: Journal of Library and Information Science, 2023)
The study examined users’ satisfaction with use of national library of Nigeria-Calabar Branch. To accomplish the research purpose, four research questions were formulated to guide the study. The survey research design was adopted and the population of the study was five thousand five hundred and forty (5540), while a sample of five hundred and fifty four (544) users of the institution were selected through random sampling technique and used for the study. The findings revealed that: Users satisfaction with library services and library resources in national library was significantly high. Based on the findings the following were recommended: National libraries should be stocked with current and up-to-date materials in order to encourage researchers to use their facilities and National library services should be adequate for the needs of national library users, it is most likely that the library will be heavily used.